Noncomplicated Excision of a Mobile Pedunculated Septal Hemangioma of the Left Ventricle - Mazen, Mahmoud (Am J Case Rep, 2016)
Patient: Female, 27 Final Diagnosis: LV hemangioma Symptoms: Palpitation • dyspnea • fatigue Medication: — Clinical Procedure: Posterior atriotomy Specialty: Cardiology OBJECTIVE: Rare disease BACKGROUND: Cardiac tumors are quite rare, and differential diagnosis of them is challenging. CASE REPORT: A young lady with a history of palpitations, dyspnea, and fatigue was proven by transthoracic echocardiography and cardiac magnetic resonance imaging to have a mobile left ventricular mass with rounded contour attached to the mid-part of the interventricular septum. The mass was approached via a posterior inter-atrial approach to avoid left ventriculotomy and provide adequate exposure to completely excise the tumor and control its pedicle with minimal cardiac trauma. Histological examination of the mass was diagnostic of capillary and sinusoidal hemangioma. CONCLUSIONS: Complete excision of cardiac hemangioma is recommended once it is diagnosed, for histopathologic diagnosis and because of the possibility of serious complications.